PERSEPSI WISATAWAN MENGENAI KAWASAN KONSERVASI PENYU PERAIRAN KOTA PARIAMAN PROVINSI SUMATRA BARAT - Essa Wahyuni Syaputri; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Tourism in Pariaman City this year to year continue to increase because of local city government in the effort of development of tourism sector, Pariaman City has a sloping beach with beautiful charm, now tourist resort has been fixed by the government of Pariaman City. In Kota pariaman there is also a turtle conservation area located on the edge of the beach gig in the village apar. Therefore, this research is conducted to find out how Tourist Perception Regarding Marine Water Turtle Conservation Area of West Sumatra Province Pariaman.This study aims to find out how the marine turtle conservation area and know how Tourist Perception Regarding Marine Water Turtle Conservation Area of West Sumatra Province Pariaman. This study uses quantitative descriptive method to examine the issues raised by analyzing the gaze of tourists who come to visit the Conservation Area. The questionnaires were distributed as many as 30 people. While data collection techniques in this study using observation, interviews, questionnaires, and documentation.Turtle Conservation of Pariaman City conducts operational activities by monitoring the location of turtle nesting habitat located along the coastline including island owned by Pariaman City. Its main function is to protect the life of diversity of flora and fauna and sustainable useKeywords: Area, Conservation. City of Pariaman